An outbreak of Neopestalotiopsis sp. causing red leaf spot of sapota in Bangladesh (Bangladesh Journal of Plant Taxonomy, 2025)
Sapota (Manilkara zapota is an economically important fruit crop in Bangladesh that was affected by the  different types of red colored leaf spot symptoms from 2019 to 2021. The study aimed to characterize red colored leaf spot symptoms of sapota by morphological and molecular analysis. Infected sapota were collected from three southern coastal districts of Bangladesh. Causal organism of the disease was isolated for morphological and molecular characterization. After 24 months of the plantation, about 70% disease prevalence in the experimental areas was recorded. The present investigation suggested that symptoms were caused by Neopestalotiopsis sp. Phylogenetic analysis using the internal transcribed spacer (ITS) region of ribosomal DNA additionally confirmed Neopestalotiopsis sp. in red leaf spot symptoms of sapota. For further validation, a pathogenicity test was carried out using three isolates on six months old saplings under Net-house conditions, and same symptom was developed in  inoculated leaves after 14 days inoculation. The present investigation confirmed the outbreak of sapota red leaf spot disease, caused by Neopestalotiopsis sp. in Bangladesh.Bangladesh J. Plant Taxon. 32(1): 53-64, 2025 (June)